Connecting Cambodia's SMEs to regional value chains: The "bridging gap" and "missing link" - Kha Sok; Runsinarith Phim; Socheat Keo; Veara Kim (Asian Development Bank Institute (ADBI), 2020)
The vision of connecting Cambodia to regional and global value chains (GVCs) is not new but the result of decades-old strategic decisions about the future. Since the return to a market-oriented economy in 1989, Cambodia has pursued policies and reforms to integrate itself into the GVCs by modernizing its industrial structure. These efforts have brought domestic small and medium-sized enterprises (SMEs) into public policy attention. The term "connecting" implies the existence of "gaps" to be linked or bridged. Gaps exist in many forms at various levels of public and private sector capacity domains. This paper discusses the current situation of SMEs in Cambodia, identifies what has worked (the "bridging gap") and what has not (the "missing link") in terms of promoting their value chain participation, and argues that while the growing reform momentum is showing signs of narrowing certain gaps, our assessment highlights the remaining or even widening gaps that are the products of dissonant fundamental constraint issues facing SMEs. The paper also offers perspectives on (1) emerging lessons learned for successful GVC engagement, and (2) implications of the evolving world, i.e., the regional cooperation and integration landscape and dramatic development in digital technology, for Cambodia's path toward connecting the country's SMEs to the GVCs.
Keywords: F14; F15; O53; 330; regional and global value chains; GVC; Cambodia; SMEs; bridging gaps; missing links